Simultaneous Determination of Potassium Sorbate, Sodium Benzoate, Quinoline Yellow and Sunset Yellow in Lemonades and Lemon Sauces by HPLC Using Experimental Design - Zor, Sule Dinc; Asci, Burge; Donmez, Ozlem Aksu; Kucukkaraca, Dilek Yildirim (OXFORD UNIV PRESS INC, 2016)
In this study, development and validation of a HPLC method was described for simultaneous determination of potassium sorbate, sodium benzoate, quinoline yellow and sunset yellow. A Box-Behnken design using three variables at three levels was employed to determine the optimum conditions of chromatographic separation: pH of mobile phase, 6.0-7.0; flowrate, 0.8-1.2 mL min(-1) and the ratio of mobile phase composed of a 0.025 M sodium acetate/acetic acid buffer, 80-90%. Resolution was chosen as a response. The optimized method was validated for linearity, the limits of detection and quantification, accuracy, precision and stability. All the validation parameters were within the acceptance range. The applicability of the developed method to the determination of these food additives in commercial lemonade and lemon sauce samples was successfully demonstrated.
Keywords: PERFORMANCE LIQUID-CHROMATOGRAPHY; SYNTHETIC FOOD COLORANTS; CAPILLARY-ELECTROPHORESIS; SOFT DRINKS; DYES; TARTRAZINE; FOODSTUFFS; BEVERAGE; PRESERVATIVES; COLUMN; Biochemistry & Molecular Biology; Chemistry